PENGARUH METODE KWL (KNOW, WANT TO KNOW, LEARNED) TERHADAP PEMBELAJARAN DOKKAI TINGKAT III PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU TAHUN AJARAN 2016/2017 - Narsih, Dewi; Widiati, Sri Wahyu; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to determine student learning outcomes before and after using KWL method and to find out the influence of KWL method on students’s ability in reading comprehension Japanese text (Dokkai) by the third level students of Japanese Education Department Faculty of Teacher’s Training and Education Riau University. This research used quasi experimental research with one group pretest - posttest design. The object of this research are 16 third level students of Japanese Education Department Faculty of Teacher’s Training and Education Riau University Academic Year 2016/2017. Data collection was performed by giving test (pretest and post test). The given test was 3 essay and 6 questions shaped is matching vocabulary, essay to find out the students’s ability in reading comprehension (pretest and post test). On average pretest results obtained by the students was 50,31 and at posttest increased by 5,61 into 55,92. Then the pretest and posttest results processed using statistical test by paired sampling t-test using software of SPSS Version 19 to get the value of the significant of the application KWL method. Based on statistical calculations for the t-test using SPSS for Windows software version 19 with paired sample test found significant numbers 0,039 lower than 0.05 ( 0.039 < 0.05 ). It means that Ha is accepted and Ho is rejected, so there is a significant impact with the application of KWL method on the learning of Japanese reading comprehension (dokkai) by the third level students of Japanese Education Department Faculty of Teacher’s Training and Education Riau University. Thus, it can be concluded that KWL method was effective in reading comprehension japanese text (dokkai). Key words: dokkai, method, KWL